Affecting children’s knowledge about rational use of medicines using read-along videos of pictorial storybooks - Bakaruddin, Syafi’ah; Mohd Noordin, Zakiah; Karuppannan, Mahmathi (Frontiers in Pharmacology, 2022)
Although efforts have been taken to educate the public about medication from a very young age, there are very limited availability and accessibility of education material for children. This study aims to assess the impact of pictorial storybooks on children’s knowledge on rational use of medicines via read-along video. This study compared pre and post knowledge scores in a nonrandomized, one-group pre-test-post-test experimental design. Pre-recorded read-along storytelling videos were used as intervention covering two topics on rational use of medicine -medicine storage and antibiotic resistance. The questionnaire and intervention videos were distributed using Google Forms to children aged 6 and 7 in Malaysia via online social media platforms. 521 children completed the study. The mean baseline knowledge score for medication storage was 4.89 (SD = 1.12) pre-test and 5.44 (SD = 0.78) post-test while for antibiotic resistance the mean was 3.616 (SD = 1.340) pre-test and 4.820 (SD = 1.134) post-test. A Wilcoxon signed-rank test showed statistically significant changes on medication storage (Z = -10.21, p < 0.001) and antibiotic resistance (Z = -14.869, p < 0.001) related knowledge among children. Pictorial storybook read-along video interventions were shown to be effective in improving children’s knowledge on rational use of medicine. Education and awareness on the use of antibiotics should be prioritized.